Antibacterial Flavonoids and Other Compounds from the Aerial Parts of Vernonia guineensis Benth. (Asteraceae). Issue 9 (3rd September 2020) - Collins Njonte Wouamba, Steven; Mouthé Happi, Gervais; Nguiam Pouofo, Michel; Tchamgoue, Joseph; Jouda, Jean‐Bosco; Longo, Frida; Ndjakou Lenta, Bruno; Sewald, Norbert; Fogue Kouam, Simeon
Abstract: An extensive phytochemical study of the aerial parts of Vernonia guineensis Benth. (Asteraceae) led to the isolation of a new flavone, vernoguinoflavone and a naturally isolated glycerol ester, eicosanoic acid 2‐hydroxy‐1, 3‐propanediyl ester, together with eighteen known secondary metabolites including quercetin, luteolin, vernopicrin, vernomelitensin, β ‐amyrin, oleanolic acid, ursolic acid, lupeol, betulinic acid, β ‐carotene, a mixture of stigmasterol and β ‐sitosterol, β ‐sitosterol‐3‐ O ‐ β ‐D‐glucoside, 2, 3‐dihydroxypropyl heptacosanoate, pentacosanoic acid, docosan‐1‐ol, tritriacontan‐1‐ol, and heptatriacontan‐1‐ol. Eleven compounds are reported herein for the first time from this species. The structures of these compounds were elucidated on the basis of extensive spectroscopic analyses, particularly 1D and 2D NMR, and HR‐ESI‐MS and by comparison of their data with those reported in the literature. The crude extract, fractions and some isolated compounds were evaluated for their antibacterial activity against Gram‐negative bacteria: Escherichia coli (ATCC 25922), Shigella flexineri (NR 518), Salmonella muenchen, Salmonella typhimurium and Salmonella typhi (ATCC 19430). All the tested compounds demonstrated inhibitory activities against the tested enteric bacteria with MIC values ranging from 3.12 to 100 μg/ml. Three flavonoids isolated from the most active fraction demonstrated the best bioactivities against Escherichia coli, Salmonella muenchen and Salmonella typhimurium with MIC values ranging from 3.12 to 25 μg/mL. Abstract :